Effect of Rayleigh backscattering on the multiwavelength random fiber laser bandwidth - David A.P.; Sulaiman A.H.; Abdullah F.; Ismail A.; Jamaludin M.Z.; Yusoff N.M. (Institute of Physics, 2024)
We investigated the effect of Rayleigh backscattering on the bandwidth of a multiwavelength random fiber laser (MWRFL). This MWRFL is based on an erbium-doped fiber amplifier (EDFA) as the gain medium and a Lyot filter as the wavelength-selective device. A high number and stable lasing line is generated with the assistance of a nonlinear polarization rotation effect induced by highly nonlinear fiber (HNLF) and optimized by a polarization controller. Longer single-mode fiber (SMF) produces wider multiwavelength bandwidth as compared to shorter SMF lengths, as 10 km, 3 km, and 0.1 km obtained 6.24 nm, 5.76 nm, and 2.75 nm wavelength bandwidth, respectively. When the SMF is removed from the setup, no Rayleigh backscattering is provided in the cavity, which led to a narrower multiwavelength bandwidth of 2.69 nm. Subsequently, the alteration of EDFA power, half-wave plate (HWP) angle, and quarter-wave plate (QWP) angles affected the degradation of multiwavelength performance. The best output spectrum is achieved at an EDFA power of 18 dBm, a HWP angle of 60, and a QWP angle of 105. The laser stability over a period of 120 min was excellent with a peak power deviation of 1.33 dB. 2023 IOP Publishing Ltd.